Pengaruh Perkembangan Teknologi Terhadap Cara Mendidik Anak Dan Dampaknya Terhadap Budget Keuangan Keluarga Muslim - Muyassarah Muyassarah (LPMP Imperium, 2019)
The purpose of this study was to determine the effect of the development of technology that is currently facing post truth on how to educate children and their impact on family financial budgets. The research is qualitative and the object of this research is Karangjoho Semarang. This writing method uses a variety of forms such as interviews, documentation, observation and literature review is useful for digging data. Analysis of the researcher uses creative criticism by pacing between methods and literature then concluding. The results of this study are children sholeh sholekah the results of Islamic religious education in the family in the midst of increasingly sophisticated technological developments even faced with the phenomenon of post truth social media internet can not distinguish true or false information, the more dangerous the children and how far the delinquency of the child influences family financial budgeting. Children's education in accordance with Islamic teachings is very important in the midst of rapid modern technology so that their children become human beings and are able to face complex problems in society. The implication of the research is that adulthood and good character in children will produce a comfortable life for parents, then the amount of family financial expenditure will not occur, but vice versa if bad children fall into the dark world of using technology with various forms of delinquency and parents are wrong to educate, then a lot of family financial expenses will be spent. KEYWORDS: Technological development, educating children, family financial budget